Verbal memory productiveness in a two-language system - Jacikevičius, A. (Psichologija, 1965)
Verbal memory productivity in a single-language system has been studied in many dimensions in the works of H. Ebinhauzas, A. Nečiajevas, A. Smirnovas, P. Zinčenka, and other Soviet and foreign psychologists. However, the research does not reveal bilingual people’s verbal memory patterns. This article summarizes the experimental results obtained investigating verbal memory in a two-language system (Lithuanian and Russian). Here are some results of available data based on eighth grade students of Lithuanian schools under identical conditions of perception: they remember 24.6% less verbal material in a second language (Russian) than their native Lithuanian; a first year remembers 22% less material in his second language than in his first, but Lithuanians studying Russian language and literature remember 0.7% more of what they learn in Russian by the fifth year of study. This shows that the measures of verbal memory of a second language are less productive for as long as a given language is not finally learned. Research has shown that learning a new language is not detrimental to the productivity of verbal memory. People who command two languages well can equally remember and reproduce a wide range of oral information in either language. Intraverbal communications in both languages are necessary for the successful transfer of remembered material from one language to another.